Carbon stock dynamics in Ethiopian forests; a systematic review for sustainable forest management towards climate change mitigation - Melkamu Kassaye; Etsegenet Emiru; Yonas Derebe; Alemu Tsega (Trees, Forests and People)
Forest resources play a role in mitigating climate change; however, effective mitigation requires comprehensive scientific investigation. Numerous studies prove that forests sequester CO2; however, formulating strategies and objectives from disparate evidence is challenging and demands a comprehensive review of recent research. Consequently, we employed PRISMA to investigate the dynamics of Ethiopia's forest carbon pool through the analysis of 113 studies. The studies reveal that 19 optimal allometric equations were developed for different forest scenarios, highlighting the effectiveness of DBH as a predictive variable. Moist montane forests reveal the highest forest carbon pool, measured at 693.1 Mg/ha. Participatory forest management enhances the ability of forests to sequester carbon by 33 % through sustainable practices. The natural forest showed the highest carbon density among various forest types, recorded at 394.58 Mg/ha. Woody biomass carbon stock accounted for the largest portion of biomass at 62.2 %, whereas soil organic carbon comprised 35.6 %. From the included studies we suggest that effective sustainable forest management in Ethiopia calls for the examination of land use changes and the evaluation of diverse forest scenarios to improve forest carbon sequestration capabilities, thus contributing to national and international efforts and commitments of climate change mitigation.